The Role of Memorable Tourism Experiences in the Relation between City Image and Visitor Engagement Toward Re-Visit Intention to Yogyakarta City - Ahsanah, Ulfah; Artanti, Yessy (Universitas Muhammadiyah Yogyakarta, 2021)
Research Aims: The purpose of this paper is to analyze and discuss the influence of city image and visitor engagement on re-visit intention through memorable tourism experiences as a mediation variable.Design/Methodology/Approach: The research sampling techniques used was nonprobability sampling by judgmental sampling methods. The respondents involved 220 visitors who had visited Yogyakarta city two times in the last two years. Path analysis was employed to analyze the dataResearch Findings: The results showed that visitor engagement had no significant impact on re-visit intention, while city image and memorable tourism experiences significantly affected re-visit intention. Similarly, city image and visitor engagement significantly influenced memorable tourism experiences.Theoritical Contribution/ Originality: The empirical results of this study provide tenable evidence that the proposed Path analyse designed to consider city image visitor engagement, memorable tourism experience, and revisit intention simultaneously is acceptable, although the previous researchers have not explained the relationship between variables as a wholePractitioner/Policy Implication: The results of this study indicate that the city of Yogyakarta is able to sell and market the image of the city and its tourism performance related to culture well to tourists, so that tourists have long-term memorable memories related to the city of Yogyakarta, especially women aged 15-30 years, even though based on the research results there is no emotional attachment to tourists when traveling to Yogyakarta.Research Limitation/Implication: In conducting this research, the researchers have limitations in data retrieval due to a COVID-19 outbreak that made many tourists not visiting tourist destinations, resulted in tourism-related groups even quieter and online questionnaires could not spread properly.